Female Worker Balance: Social Media Balance and Family Support - Badrianto, Yuan; Astuti, Dwi (Jurnal Multidisiplin Madani, 2023)
This study examines the influence of social media balance and family support on the balance of female workers in the Bekasi area. The population in this study involved women who work in various sectors and are active on social media. A total of 96 respondents were selected through random sampling method from various social media user community groups. Data was collected through questionnaires distributed online, relying on a Likert scale to assess respondents' perceptions. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the Smart PLS program. Results show that social media use balance and family support have a significant influence on female workers' work-life balance. The findings highlight the importance of effective time management on social media platforms and the role of family support as key factors in achieving balance between work demands and domestic responsibilities. This research provides important insights for companies, HR practitioners, and policy makers to develop initiatives and programs that support the well-being of female workers, especially in the context of increased pressure from social media and the need for ongoing family support